Distribution of the Laterally Supplying Facial Nerve to the Orbicularis Oculi Muscle. (11th July 2020) - Choi, Yeop; Kim, In-Beom
Abstract: Background: The facial nerve that traverses the lateral border of the orbicularis oculi muscle is considered the primary motor for the muscle. Nevertheless, the lateral motor supply to the orbicularis oculi muscle has not yet been fully described. Objectives: The aim of this study was to report detailed anatomic information about the lateral motor supply route to the orbicularis oculi. Methods: Facial nerve branches that cross the lateral orbicularis oculi border were fully traced from the parotid border to the nerve destinations in 43 fresh hemifaces by microscopic surgical dissection and time-lapse photography. Results: Through the lateral route, the anterior temporal and upper zygomatic branches supply the superior orbital and superior preseptal orbicularis oculi of the upper eyelid, as well as the lateral pretarsal and malar orbicularis oculi, excluding the upper medial pretarsal portion of the upper eyelid and most of the lower eyelid. The nerve supplying the lateral pretarsal orbicularis oculi muscle crosses the anterior area of the zygomatic arch. It then traverses an area 6 mm above and 4 mm below the lateral canthal crease. Conclusions: The anterior area of the zygomatic arch and an area 6 mm above and 4 mm below the lateral canthal crease are the facial nerve danger zones. The present anatomic findings provide surgeons with further insights for performing blepharoplasty, midface lift, facelift, and facial nerve reconstructive surgery.